Gender Aspects of the Trade and Poverty Nexus : A Macro-Micro Approach - Bussolo, Maurizio (Washington, DC: World Bank and Palgrave Macmillan, 2013)
This report is on the findings of a major international research project examining the links between trade, gender, and poverty. Trade liberalization can create economic opportunities, but women and men cannot take advantage of these opportunities on an equal basis. Women and men differ in their endowments, control over resources, access to labor markets, and their roles within the household. It may seem obvious that gender differences play an important role in transmitting the effects of trade expansion to poverty, especially in less developed countries, where gender inequality is usually more pronounced. Although the literature includes numerous analyses on the links between trade and poverty and between gender inequality and poverty, it seems not to have combined these two sets of studies in a consistent empirical framework. The main objective for the research project documented in this book was to fill, at least in part, this gap in the literature. This report describes the simplest conceptual framework that can be used to analyze the linkages between trade and poverty through gender. It includes two parts. The first, based on standard international trade models, considers the linkages between trade and gender. The second, based mainly on the microeconomic models of household behavior, deals with the linkages between gender and poverty.